The Reality of Betawi Culture in the Film "si Doel the Movie" (Semiotic Analysis of Roland Barthes) - Tofa, Tofa (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to interpret and describe the reality of Betawi Sarong culture in the film "Si Doel the Movie" and to find out the meaning of denotation, connotation, and myth in this film. This research uses qualitative and descriptive methods and semiotic analysis of Roland Barthes. In this case, Roland Barthes' semiotic analysis begins with the denotation meaning, which is the real meaning, then the connotative meaning, which has a double meaning. The connotation meanings attached and believed by the public will eventually become myths. The results obtained from this research from scenes related to the reality of Betawi culture in society in everyday life produce several concepts, namely that there is a shift in stigma and stereotypes towards Betawi people who are trying to be overturned by Doel's character who shows a calmer attitude in acting and speaking, like the character of non-Betawi people. Stigma and stereotypes that make Betawi people seem to be marginalized, through the character of Doel's figures, are shifted to become educated Betawi people. Meanwhile, from the scenes related to the concept of representing the identity and existence of the Betawi sarong, the concept is that the role and function of the sarong, in this case, is ultimately determined by the owner or user related to emotional ties and other elements of the culture, where the sarong can change its function according to changes, which underlies its initial function.